Rapid Improvement in Cardiac Damage Predicts Better Prognosis After Transcatheter Aortic Valve Replacement - Hao-Wei Lee; Chih-Hui Chin; Po-chin Chou; Chia-Hsiu Chang; Chiu-Ling Tsai; Chi-Hung Huang (Journal of Cardiovascular Development and Disease)
Background: A staging system based on cardiac damage for severe aortic stenosis (AS) has been validated for prognosis prediction following transcatheter aortic valve replacement (TAVR). Our study aims to investigate whether TAVR can lead to changes in cardiac damage shortly after the procedure and how these changes impact prognosis. Method: Patients in this retrospective cohort study were classified into five stages (0–4) before TAVR based on the echocardiographic findings of cardiac damage. The closest echocardiogram after TAVR was used for restaging cardiac damage. The primary composite outcome was all-cause mortality or hospitalization due to heart failure (HF). Results: A total of 64 patients were enrolled (53.1% male, mean age 81.7 ± 7.7 years). Within a mean interval of 4 days (interquartile range = 3 to 7 days) after TAVR, cardiac damage improved in 25.0% of patients, while it worsened in 20.3%. During a median follow-up of 2.5 ± 1.9 years, 34.4% of patients met the primary endpoint, which included 16 deaths and 6 HF hospitalizations. Cox regression analysis revealed that improvement in cardiac damage correlated with a lower risk of composite death or HF hospitalization (HR: 0.095; 95% CI: 0.014–0.627; p = 0.015). Conclusions: TAVR can lead to changes in cardiac damage over a short period in patients with severe AS, and rapid improvement in cardiac damage after TAVR is associated with a better prognosis.